Application of magnetic analyzers for detecting carburization of pyrolysis furnace tubes - Du, Chenyang; Liu, Chang; Li, Xiaowei; Liu, Baolin; Lu, Jianyu; Tan, Xinli; Song, Ce (Frontiers in Materials, 2023)
Ethylene pyrolysis furnace is a key equipment in the ethylene production industry with the pyrolysis furnace tube being the core component of the system. The tube operates at high temperature (950°C–1,100°C) and hydrocarbon medium for a long time, and the Cr35Ni45Nb centrifugal casting alloy material is often chosen as the material of the tube. Due to its harsh working conditions, its common failure issues include carburization, high-temperature creep cracking, thermal shock and thermal fatigue, overheating, creep expansion, bending, etc. Among them, carburization is the main cause of furnace tube failure. In this work, based on the characteristics of HP series (ASTM HP grade) furnace tube material, which is transformed from paramagnetic material to ferromagnetic material following carburization, the cracking furnace tube with different carburization layer thickness has been prepared, and the coercivity of furnace tube with different thickness of carburization layer is tested by magnetic analyzer. The relationship curve between carburization layer thickness and coercivity is subsequently studied to find a means to test the carburization layer thickness in engineering. By fitting the experimental data, the fitting rate reached 97%, which in turn verified the validity and accuracy of the method.